Journal of Emergency Nursing March 2011 Vol.37, no.2 - Redaksi (Elsevier, 2011)
-The process of acquiring practical knowlagde by emergency nursing professionals in Taiwan: A phenomenological study -Assessing emergency nurses' geriatric knowladge and perceptions of their geriatric care -Do patients understand discharge instructions? -...